The protective impacts of lipoic acid on diclofenac-induced hepatorenal toxicity in broiler chicks - Marwa R. Abdul-Ghani; Ahmed S. Naser (Iraqi Journal of Veterinary Sciences, 2022)
Alpha-lipoic acid is an anti-inflammatory and antioxidant compound that shows free radical scavenging actions and potent antioxidant properties on the metabolites of other cellular oxidants. The investigation of the defensive activity of alpha-lipoic acid (ALA) counter to diclofenac triggered liver and kidney damage in broiler chicks was the goal of this research. Chicks (7 days old) were distributed into four groups of six chicks each. The first group was the control received propylene glycol, the second group was injected intraperitoneally with Alpha-lipoic acid 80 mg/kg, the third group was injected intraperitoneally with diclofenac sodium at a dose of 2 mg/kg, and the fourth group was treated with ALA at 80 mg/kg and diclofenac at 2 mg/kg together. The trial continued for seven days. One day after the latest treatment, all the chicks were sacrificed by cutting jugular veins; blood samples were taken for biochemical analysis. Diclofenac causes a significant increase in ALT, AST, creatinine, and urea, while the coadministration of ALA with Diclofenac caused a significant decrease in ALT, AST, Creatinine, and Uric acid. Alpha-lipoic acid may benefit from counteracting diclofenac-induced hepatorenal toxicity due to antioxidant effects.